PELATIHAN DAN SOSIALISASI ISAK 335 PADA PANTI ASUHAN SOLOMASI - sahala purba; Elperida Juniarni Sinurat; Kuras Purba; Wie Shi Wudjud; Dame TM Nababan (LPPM Universitas Abdurrab, 2026)
The main objective of the community service projection is to assist all orphanages in Indonesia, focusing on orphanages in Medan City, in using ISAK 335 to prepare their financial reports. This will help build trust among several large donors regarding the management of their donations to the orphanage. The service method that we use is The approach used in this training program begins with an initial interview, in this service the number of interviewees is 2 people, namely the direct owner of the orphanage. And training is conducted for 3 people, namely employees of the orphanage. The training is conducted on how to make accounting records and prepare financial reports in accordance with regulations in Indonesia, namely comprehensive income statements, statements of changes in net assets, statements of financial position, cash flow statements. The time of training and socialization was carried out on December 14, 2025. The results of this service are showing that the orphanage managers feel uncomfortable because previously they were not aware of the financial reporting standards specifically for their institutions. They only keep records as a simple list of income and expenses, which is even displayed openly on the orphanage's notice board. The results of this community service show that orphanages only document their finances as basic cash inflows and outflows, without complying with the required accounting standards. The recommendations we suggest for orphanages throughout Indonesia, especially for the Solomasi orphanage, are that the implementation of financial reporting in accordance with accounting standards is expected to increase transparency and accountability in fund management, strengthen donor trust, and open wider funding opportunities, both from companies and foreign donors, thereby supporting the sustainability and development of orphanages professionally.